Noel Rosa Pau-Brasil : poesia como falamos - Andrade, Ênio Bernardes de (2017)
This research proposes the study of Noel Rosa's songs according to the precepts of the Pau-Brasil poetry by Oswald de Andrade. Through the analysis of works from Noel’s songbook, such as Conversa de botequim, Gago apaixonado and Três apitos, it can be noticed that the so called “Poeta da Vila” materialized the practice of poetry "as we speak" promulgated as a gesture of rupture by the Manifesto da Poesia Pau-Brasil. Besides the use of a colloquial and current language among everyday facts, this approach is not restricted to the text, passing through the observation of two fundamental points. The melodies of the songs camouflage the speech intentions by means of the intonative resources, constituting a way of singing, speaking singing, according to the semiotic theory by Luiz Tatit; The songs realizes themselves as well as the speech, by the voice. They are captured by the ear without the writing intermediation, incorporating the vocal nuances beyond the word at the same time that they constitute a performative act which involves the scenes’ dramatization, the musical instrumentation , space and the listener, constituting a corporal reception, according to the Paul Zumthor theoretical perspective. Noel Rosa is observed as a matrix of an aspect in which this proximity to the speech occurs more clearly, as it can be seen in his simple and direct texts melded into the melodies’ intonation, so as in the vocal interpretation of the songs, especially when he is the interpreter himself. The “Poeta da Vila” is compared to the Oswald de Andrade’s work aspects by the use of resources such as humor and parody opposed to the seriousness of the doctors' offices, such as the incorporation of the urban landscape into an updating process of the artistic practices to the modernity of the 20th century. It is observed that despite the convergences, the two authors’ universes did not intersect in their time, in which the song was not perceived in the great arts category. However, in the 1960s, songwriters as Chico Buarque and Caetano Veloso were identified as the main poets of their generation, with Noel Rosa and Oswald de Andrade. In view of the difference in Noel Rosa’s work perception as representative or not of his time poetry, so as the presence of the composers of song pointed out among the roll of the great poets from the 1960 decade , a scene of imprecision in the song understanding as poetic language is configured.